Development and validation of finite element impact models of high-density UAS components for use in air-to-air collision simulations. Issue 13 (1st July 2020) - Kota, Kalyan Raj; Ricks, Trent; Gomez, Luis; Monteros, Jaime Espinosa de los; Olivares, Gerardo; Lacy, Thomas E.
Abstract: Understanding the severity of mid-air collisions between lightweight fixed-wing unmanned aerial systems (FW-UASs) and manned aircraft is a critical flight safety issue. Finite element models of high-density FW-UAS components were developed and validated; such components are particularly damaging during air-to-air collisions. FW-UAS motors and batteries were launched into semi-monocoque 2024-T3 targets using a compressed gas gun. Material/geometric nonlinear simulations of each impact were performed and correlated with physical test results. Predicted skin penetrations/perforations, projectile residual velocities, strain-time histories, and target forces matched experimental observations. Validated component models will be integrated into high-fidelity air-to-air collision simulations involving FW-UASs and manned aircraft.